CD44v6‐peptide functionalized nanoparticles selectively bind to metastatic cancer cells - Li, Linxian; Levkin, Pavel (Advanced science, 2017)
CD44v6 peptide functionalized nanoparticles are fabricated in a facile and controllable way to selectively bind to CD44v6 positive tumor cells with highly efficient anticancer and antimetastatic properties. The reported modular synthesis and facile preparation makes this system highly potent for developing novel multifunctional nanocarriers for therapeutic and/or diagnostic anticancer applications.